The Impact of the SPAWN Strategy on Developing Self-Regulation Skills for Fine Arts Institute Students (Journal of the College of Basic Education, 2025)
The aim of the research is to identify the effect of the SPAWN strategy (s.p.a.w.n) in developing self-regulation skills in the viewing material among students of the Institute of Fine Arts. To achieve this, the researcher adopted the complete experimental design. The research community was determined by the students of the Institute of Fine Arts for Boys in the morning, affiliated with the General Directorate of Education of the First Karkh. The random sample was chosen by lottery for the institute. Then, the third-year students of the audio-visual department were chosen to represent one of them, the experimental group, numbering (15), which studied according to the (SPOWN) strategy, and the other, the control group, numbering (15), which studied according to the traditional method. Among them is the alpha-Cronbach equation, Wilcoxon test, Man Whitney test, item difficulty treatment, item discrimination equation. The researcher reached results including: the presence of statistically significant differences at a significance level of (0.05) between the average ranks of the scores of the experimental group who study according to the (SPOWN) strategy and the average ranks of the scores of the students who study according to the traditional method in self-regulation skills in favor of the experimental group. The two research groups were rewarded in a number of variables, namely: chronological age, Raven’s intelligence test, fathers’ academic achievement, and mothers’ academic achievement. The two research tools were constructed, namely a cognitive test of the observed material and a scale of self-regulation skills, which consisted of (40) multiple-choice items. The validity and reliability of both tools were confirmed, and statistical methods were adopted. In light of the above, a number of conclusions, recommendations and proposals were reached. The research summarized: The aim of the research was to identify the effect of the SPAWN strategy (s.p.a.w.n) on developing self-regulation skills in viewing material among students of the Institute of Fine Arts.